Host Galaxy and Nuclear Properties of IR-selected AGNs with and without Outflow Signatures - Gabriel A. Oio; Y. Sophia Dai; C. G. Bornancini; Zi-Jian Li (The Astrophysical Journal, 2024)
Active galactic nucleus (AGN) driven outflows can have a significant impact on the evolution of the host galaxy. In this work, we compare the properties of galaxies that host AGNs with and without outflows. Our sample consists of 103 AGNs identified by mid-IR color–color selection and confirmed with optical spectroscopy at a redshift range of 0.3 ≲ z ≲ 0.9. We fit the [O iii ] λ 5007 line using spectra from the zCOSMOS survey to identify and study the occurrence of outflows. We find that ionized outflows are present in ∼25% of our sample, with the largest incidence at the highest [O iii ] and X-ray luminosity bins. The fastest outflows are found in the more extended and massive galaxies. We do not observe a difference in the star formation rate of AGNs with outflows compared to AGNs without outflows. From visual inspection and nonparametric morphological studies, we obtain that outflows are preferentially observed in galaxies with disk-type and elliptical morphologies.